2018
DOI: 10.1177/1053815118760314
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Email to Coach Early Childhood Teachers

Abstract: The purpose of this study was to evaluate the use of performance-based feedback (PF) delivered via email on early childhood teachers’ sustained use of recommended practices within inclusive early childhood classrooms. A multiple baseline design across behaviors was replicated across three teachers to examine the relation between PF delivered via email and teachers’ use of target recommended practices across settings, over time, and during covert observations. Results indicated PF delivered via email was an eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
1
18
0
Order By: Relevance
“…Another study have been carried out by Barton et al (2018) to evaluate the use of learning materials and tasks delivered via email which teachers recommended within inclusive early childhood classrooms. Results indicated that teaching and learning through email was an effective method for increasing teachers' use of target behaviors; however generalization and maintenance varied across teachers.…”
Section: Flexiblementioning
confidence: 99%
“…Another study have been carried out by Barton et al (2018) to evaluate the use of learning materials and tasks delivered via email which teachers recommended within inclusive early childhood classrooms. Results indicated that teaching and learning through email was an effective method for increasing teachers' use of target behaviors; however generalization and maintenance varied across teachers.…”
Section: Flexiblementioning
confidence: 99%
“…Training paired with TEPF and face-to-face feedback has been used by researchers to enhance teachers' use of effective teaching practices, such as social emotional practices (Snyder et al, 2018), language practices (Ota & Austin, 2013), descriptive praise (Hemmeter et al, 2011), and recommended practices (Barton et al, 2018). Although TEPF has improved teachers' use of target skills, teachers may need support across various types of routines to use target practices, such as communicative antecedents and consequences, with fidelity (Rahn et al, 2019).…”
Section: Professional Developmentmentioning
confidence: 99%
“…Researchers have identified PD packages that can be used within the context of early childhood classrooms (Artman-Meeker, Hemmeter, & Snyder, 2014; Barton et al, 2018; Fox, Hemmeter, Snyder, Binder, & Clarke, 2011; Hemmeter et al, 2011; Snyder et al, 2018). For example, Fox and colleagues (2011) used workshops and face-to-face coaching to support inclusive early childhood special education (ECSE) teachers’ use of pyramid model practices (Fox et al, 2011).…”
mentioning
confidence: 99%